Position statement on EUS-guided ablation of pancreatic cystic neoplasms from an international expert panel - Teoh, Anthony Yuen-Bun; Seo, Dong Wan; Brugge, William; Dewitt, John; Kongkam, Pradermchai; Linghu, Enqiang; Moyer, Matthew T.; Ryu, Ji Kon; Ho, Khek Yu (Endoscopy International Open, 2019)
Background and aim Recently, several guidelines with divergent recommendations on management of pancreatic cystic neoplasm have been published but the role of endoscopic ultrasound (EUS)-guided pancreatic cyst ablation has not been thoroughly addressed. The aim of the current paper is to explore the issues surrounding EUS-guided pancreatic cyst ablation by generating a list of clinical questions and providing answers based on best scientific evidence available.Methods An expert panel in EUS-guided pancreatic cyst ablation was recruited from members of the Asian EUS group and an international expert panel. A list of clinical questions was created and each question allocated to one member to generate a statement in response. The statements were then discussed in three Internet conference meetings between October 2016 and October 2017. The statements were changed until consensus was obtained. Afterwards, the complete set of statements was sent to all the panelist to vote on strength of the statements, classification of the statement sand grading of the evidence.Results Twenty-three statements on EUS-guided drainage of pancreatic cyst ablation were formulated. The statements addressed indications for the procedures, technical aspects, pre-procedure and post-procedure management, management of complications, and competency and training in the procedures.Conclusion The current set of statements on EUS-guided pancreatic cyst ablation are the first to be published by any endoscopic society. Clinicians interested in developing the technique should reference these statements and future studies should address the key issues raised in the document.